Efficient bio-production of citramalate using an engineered Escherichia coli strain - Webb, Joseph P.; Arnold, S. Alison; Baxter, Scott; Hall, Stephen J.; Eastham, Graham; Stephens, Gill (Society for General Microbiology, 2018)
Citramalic acid is a central intermediate in a combined biocatalytic and chemocatalytic route to produce bio-based methylmethacrylate, the monomer used to manufacture Perspex and other high performance materials. We developed an engineered E. coli strain and a fed-batch bioprocess to produce citramalate at concentrations in excess of 80 g l-1 in only 65 h. This exceptional efficiency was achieved by designing the production strain and the fermentation system to operate synergistically. Thus, a single gene encoding a mesophilic variant of citramalate synthase from Methanococcus jannaschii, CimA3.7, was expressed in E. coli to convert acetyl-CoA and pyruvate to citramalate, and the ldhA and pflB genes were deleted. By using a bioprocess with a continuous, growth-limiting feed of glucose, these simple interventions diverted substrate flux directly from central metabolism towards formation of citramalate, without problematic accumulation of acetate. Furthermore, the nutritional requirements of the production strain could be satisfied through the use of a mineral salts medium supplemented only with glucose (172 g l-1 in total) and 1.4 g l-1 yeast extract. Using this system, citramalate accumulated to 82±1.5 g l-1, with a productivity of 1.85 g l-1 h-1 and a conversion efficiency of 0.48 gcitramalate g-1 glucose. The new bioprocess forms a practical first step for integrated bio- and chemocatalytic production of methylmethacrylate.